A Prospective Comparison of EUS-Guided FNA Using 25-Gauge and 22-Gauge Needles - Imazu, H.; Uchiyama, Y.; Kakutani, H.; Ikeda, Kei-Ichi; Sumiyama, K.; Kaise, M.; Omar, S.; Ang, T.L.; Tajiri, H. (Hindawi Publishing Corporation, 2009)
Background and Aims. There are limited data on the differences in diagnostic yield between 25-gauge and 22-gauge EUS-FNA needles. This prospective study compared the difference in diagnostic yield between a 22-gauge and a 25-gauge needle when performing EUS-FNA. Methods. Forty-three patients with intraluminal or extraluminal mass lesions and/or lymphadenopathy were enrolled prospectively. EUS-FNA was performed for each mass lesion using both 25- and 22-gauge needles. The differences in accuracy rate, scoring of needle visibility, ease of puncture and quantity of obtained specimen were evaluated. Results. The overall accuracy of 22- and 25-gauge needle was similar at 81% and 76% respectively (N.S). Likewise the visibility scores of both needles were also similar. Overall the quantity of specimen obtained higher with the 22-gauge needle (score: 1.64 vs.